Analysis of the Surface Dispersion in the Mediterranean Sub-Basins - Bouzaiene, Maher; Menna, Milena; Poulain, Pierre-Marie; Bussani, Antonio; Elhmaidi, Dalila (Frontiers in Marine Science, 2020)
Surface dispersion properties give an immediate characterization of the spreading of passive and active tracers in the ocean, like pollutant and marine species. The Mediterranean sub-basins (Tyrrhenian, Adriatic, Ionian, Levantine and Aegean) are known as complex dynamic regions due to the presence of coherent structures on different motion scales. This paper focus on dispersion of the surface Mediterranean flow using the surface current data derived from two different drifter designs: the Coastal Ocean Dynamics Experiment (CODE) and the Surface Velocity Program (SVP) drifters. The absolute dispersion for small time scales (<2 days) shows similar anisotropic quasi-ballistic regimes in the five sub-basins. For intermediate time scales (2-15 days), the absolute dispersion shows the occurrence of an elliptic regime in all the Mediterranean sub-basins except in the Adriatic Sea, where the dominance of a hyperbolic regime is observed. The relative dispersion statistics show the presence of a non-local exponential regime in the Tyrrhenian sub-basin, with spatial scale smaller than the internal Rossby Radius of deformation DI. For spatial scales close to DI, two local relative dispersion regimes are found due to the influence of sub-basin scale structures: a Richardson regime in the Tyrrhenian and Aegean sub-basins and a shear/ballistic regime in other sub-basins. Furthermore, for large time scale (>15 days) and spatial scale larger than DI, our results emphasize a similarity in all the sub-basins with the presence of a quasi Random-walk regime and a quasi diffusive regime for the absolute and relative dispersion, respectively.